Nimodipine Improves Cognitive Impairment After Subarachnoid Hemorrhage in Rats Through IncRNA NEAT1/miR-27a/MAPT Axis - Li JW; Ren SH; Ren JR; Zhen ZG; Li LR; Hao XD; Ji HM (Dove Medical Press, 2020)
Jun-Wei Li, Shao-Hua Ren, Jin-Rui Ren, Zi-Gang Zhen, Li-Rong Li, Xu-Dong Hao, Hong-Ming Ji Department of Neurosurgery, The People’s Hospital of Shanxi Province, Taiyuan, Shanxi Province, People’s Republic of ChinaCorrespondence: Hong-Ming Ji Tel +86 0351-4960650Email hongmingj@sina.comBackground: Subarachnoid hemorrhage (SAH) is a cerebral hemorrhage disease that severely damages the brain and causes cognitive impairment (CI). Therefore, accurate and appropriate treatment strategies are urgently needed. The application of nimodipine can not only improve blood circulation in patients with SAH but also repair ischemic neuron injury.Purpose: To investigate the effects of nimodipine and lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1)/miR-27a/microtubule-associated protein tau (MAPT) axis on CI after SAH.Methods: One hundred and twenty healthy male rats were selected and equally divided into control group, sham operation group, model group, PBS group, nimodipine group (drug group), NC siRNA group, NC mimics group, NEAT1 siRNA, miR-27a mimics, MAPT siRNA, drug + NEAT1-ad, and drug + NC-ad groups by random number table. Rats in the model group were constructed by double-hemorrhage model, and expression vectors were injected into the tail to regulate the expression of lncRNA NEAT1, miR-27a and MAPT. In addition, Western blot was employed to detect brain tissue protein, flow cytometry was applied to measure brain tissue apoptosis, and MTT was utilized to determine cell activity, so as to evaluate brain damage and cognitive function in each group.Results: Nimodipine, down-regulated lncRNA NEAT1, up-regulated miR-27a and down-regulated MAPT all improved brain damage and CI, inhibited brain tissue cell apoptosis, and enhanced brain cell activity. The common binding sites of lncRNA NEAT1 and MAPT were found on the miR-27a sequence fragment, and miR-27a could be paired with the former two. Nimodipine was found to cause the down-regulation of lncRNA NEAT1 and MAPT, as well as the up-regulation of miR-27a.Conclusion: Nimodipine can improve CI after SAH in rats through the lncRNA NEAT1/miR-27a/MAPT axis.Keywords: subarachnoid hemorrhage, cognitive impairment, lncRNA NEAT1/miR-27a/MAPT axis, nimodipine